The Transmission and Use of the Collected Legal Decisions of Sir Richard Maitland of Lethington in Sixteenth- and Seventeenth-Century Scotland. (14th August 2018) - Wilson, Adelyn L M
Abstract: This article examines the textual transmission of the collected legal decisions (or practicks) of the sixteenth-century Scottish judge, Sir Richard Maitland of Lethington. It applies the method of stemmatology to the twenty extant manuscript texts to reveal their interrelationships and the manner of the text's transmission. It also shows how the copies' owners amended the text, which in turn reveals both their interests in and use of it. Finally, it shows that the significant and deliberate amendments to a copy of the text by one owner, compounded by problems in the transmission of one branch of the text descended from his copy, entirely changed contemporary perceptions of the collection.